Facilitators and Barriers to HIV Activities in Religious Congregations: Perspectives of Clergy and Lay Leaders from a Diverse Urban Sample - Mendel, Peter (Journal of religion and health, 2014)
This paper examines facilitators and barriers to HIV activities within religious congregations, the relative internal or external sources of these influences, and suggestive differences across congregational types. Results are based on in-depth interviews with clergy and lay leaders (n = 57) from 14 congregations in Los Angeles County, California, purposively selected to reflect diversity in racial-ethnic composition, denomination, size, and HIV activity level. Many common facilitators and barriers were related to norms and attitudes, only a few of which appeared overtly associated with theological orientations. Clergy support was a facilitator particularly prevalent among congregations having higher HIV activity levels, indicating its importance in sustaining and expanding HIV programs. Resource issues were also prominent, with material resource barriers more frequently mentioned by smaller congregations and human resource barriers more among larger congregations. Organizational structure issues were mostly centered on external linkages with various social service, public health, and faith-based entities. Analysis of internal versus external sources highlights the roles of different stakeholders within and outside congregations in promoting HIV activities. Potential differences across congregational types represent fruitful areas for future research.